Blocking the Hepatic Branch of the Vagus Aggravates Hepatic Ischemia-Reperfusion Injury via Inhibiting the Expression of IL-22 in the Liver - Heng Zhou; Juling Xu; Sanxiong Huang; Ying He; Xiaowei He; Lu Guo; Shi Yin; Sheng Lu (Journal of Immunology Research)
Liver ischemia-reperfusion injury (IRI) is an inevitable process during liver transplantation, hemorrhagic shock, resection, and other liver surgeries. It is an important cause of postoperative liver dysfunction and increased medical costs. The protective effects of the vagus nerve on hepatic IRI have been reported, but the underlying mechanism has not been fully understood. We established a hepatic vagotomy (Hv) mouse model to study the effect of the vagus on liver IRI and to explore the underlying mechanism. Liver IRI was more serious in mice with Hv, which showed higher serum ALT and AST activities and histopathological changes. Further experiments confirmed that Hv significantly downregulated the expression of IL-22 protein and mRNA in the liver, blocking the activation of the STAT3 pathway. The STAT3 pathway in the livers of Hv mice was significantly activated, and liver injury was clearly alleviated after treatment with exogenous IL-22 recombinant protein. In conclusion, Hv can aggravate hepatic IRI, and its mechanism may be related to inhibition of IL-22 expression and downregulation of the STAT3 pathway in the liver.